Unity in Society: Forsters Visions in A Passage to India - Petricella Margareta; Ira Rasikawati (Universitas Sanata Dharma, 2018)
A Passage to India presents the issue of the human relationship between the British and the Indians during the colonization era. The clash between two races makes cross-cultural relationship impossible to achieve. Despite the conflict, Forster believes in unity and proposes essential conditions through the narrative voice, suggesting a possibility for unity in a diverse society. Using the critical qualitative method, this study attempts to discover Forster's essential conditions of unity grounded by the theory of human basic values, which are understanding, tolerance, appreciation, and welfare of all people and for all nature. Although the essential conditions are evident, there are some reasons that restrict them, namely racial prejudice, stereotypes, and colonization. Conditions to achieve unity in a diversity as proposed by Forster will never work unless any forms of colonization are abolished.Keywords: A Passage to India, Colonialism, India, Basic Human Values